The Design and Development of a Split Type Continuous Adsorption Refrigeration System with Two Adsorbent Beds - Hu Hanying; Fang Xujun; He Wei (Zhileng xuebao)
An adsorption refrigeration system with two beds is designed and developed, which uses hot water of 85~100℃ as the driving heat source. Through the alternating adsorption and desorption of the refrigerant by two adsorption beds, the system can realize continuous refrigeration. The adsorbent beds use fin and tube structure, and the surface of the fin is coated with adsorbent, which is composited by 13X and CaCl2. The coating thickness of the absorbent is only 0.15mm, which can accelerate the adsorption / desorption rate and the heat transfer rate. The evaporator uses coil and water plate structure, and they are stepped with interval and distributed from top to bottom. This structure can ensure that the water is boiling on the surface of the heat exchangers tube. The condenser adds a non-condensable gas discharging device, and the device can discharge non-condensing gas during the system’s operation, which can ensure the high efficiency of the condenser. At the same time, the structure of the cylinder block is optimized from the aspects of strength, sealing and assembly structure. In addition, the mass recovery and heat recovery are added to the adsorption refrigeration cycle. Based on this cycle model, the performance of the system is tested，it is found that when the desorption heat source is 85 ℃ hot water, the system cooling power is 7.7kW, the coefficient of performance is 0.467, the SCP is 380W / kg, and the average power consumption is 1.23 kW.